Advancements in healthcare through 3D- printed micro and nanosensors: Innovation, application, and prospects - Sushma Dave; Hardik S. Churi; Prakash A. Vishwakarma; Anand Krishnamoorthy; Uday P. Jagtap (Hybrid Advances)
Integrating 3D printing technology with micro and nanoscale sensors has emerged as a transformative approach in healthcare, offering unparalleled opportunities for innovation and application. This review paper comprehensively explores the recent advancements in this interdisciplinary field, focusing on the synthesis, fabrication techniques, applications, and prospects of 3D- Printed micro and nanosensors in healthcare. The ideal manufacturing of sensors with intricate geometries and unique capabilities is made possible by combining 3D printing technology with micro and nanoscale sensors, completely changing the healthcare industry. This transformational strategy has resulted in the creation of highly sensitive, selective, and biocompatible sensors that enable real-time monitoring, early illness detection, and tailored drug delivery. These developments improve results, alter patient care, and optimize treatment approaches. Applications include medication administration, point-of-care testing, and diagnostics. Innovations such as portable lab-on-a-chip devices are improving these areas. Future work will concentrate on improving sensor flexibility and incorporating AI to forecast and treat new medical diseases.